Estudios cinéticos e isotérmicos para la adsorción de oro a partir de dicianoaurato usando carbón activado de raquis de banano. - Torres Iturralde, Bradlye Steve (My University, 2025)
The primary objective of this research was to evaluate the kinetic and isotherm studies for the adsorption of gold from dicyanoaurate [(Au(CN)2)−] solutions, utilizing activated carbon synthesized from banana rachis as the adsorbent material. To achieve this, activated carbon was synthesized under controlled pyrolysis conditions, the variation in the amount of gold adsorbed as a function of contact time was examined, and the adsorbent's capacity for gold adsorption was evaluated, with results fitted to isotherm models. The obtained results revealed an exceptionally high adsorption capacity for the activated carbon, with equilibrium adsorption capacities (qe) consistently exceeding 1000 mg/g, starting from a fixed initial concentration of 124.14 mg/L. These findings confirm the material's effectiveness in gold removal. In the kinetic study, a general decrease in gold concentration in the solution over time was observed, demonstrating the adsorption process. However, fluctuations were identified that necessitate careful consideration for precise fitting to conventional kinetic models. Similarly, while the isotherm showed high capacity, it exhibited an atypical trend where adsorption capacity slightly decreased with increasing equilibrium concentration, suggesting complex phenomena in the process. In conclusion, this study demonstrates that activated carbon derived from banana rachis possesses a significant capacity for gold adsorption, supporting the research hypothesis. Although particularities were observed in the kinetic and isotherm trends, possibly due to the adsorbent's high efficiency and experimental conditions, the material's promise is undeniable. These results validate its potential as a sustainable adsorbent and open new avenues for optimizing gold recovery processes, highlighting the importance of future investigations to deepen understanding of the mechanisms and refine application conditions.
La presente investigación tuvo como objetivo principal evaluar los estudios cinéticos e isotérmicos para la adsorción de oro a partir de soluciones de dicianoaurato [(Au(CN)2)−], empleando carbón activado sintetizado a partir del raquis de banano como material adsorbente. Para ello, se procedió con la síntesis del carbón activado bajo condiciones controladas, se examinó la variación de la cantidad de oro adsorbido en función del tiempo de contacto, y se evaluó la capacidad del material para adsorber oro, ajustando los resultados a modelos isotérmicos. Los resultados obtenidos revelaron una capacidad de adsorción excepcionalmente alta del carbón activado, con valores de que en el equilibrio que superan consistentemente los 1000 mg/g, partiendo de una concentración inicial fija de 124.14 mg/L. Estos hallazgos confirman la eficacia del material para la remoción de oro. En el ámbito cinético, se observó una disminución general en la concentración de oro en la solución a lo largo del tiempo, evidenciando el proceso de adsorción. Sin embargo, se identificaron fluctuaciones que requieren una consideración detallada para el ajuste preciso a modelos cinéticos. De manera similar, la isoterma, si bien mostró una alta capacidad, exhibió una tendencia atípica donde la capacidad de adsorción disminuía ligeramente al aumentar la concentración de equilibrio, lo cual sugiere fenómenos complejos en el proceso. En conclusión, este estudio demuestra que el carbón activado derivado del raquis de banano posee una capacidad significativa para adsorber oro, respaldando la hipótesis de investigación. Aunque se presentaron particularidades en las tendencias cinéticas e isotérmicas, posiblemente debido a la alta eficiencia del adsorbente y las condiciones experimentales, la promesa del material es innegable. Estos resultados validan su potencial como adsorbente sostenible y abren nuevas vías para la optimización de procesos de recuperación de oro, destacando la importancia de investigaciones futuras que profundicen en los mecanismos y afinen las condiciones de aplicación.
Keywords: KINETICS; THERMAL ISOMETRY; ACTIVATED CARBON; CINETICA